PENGARUH BRAND AMBASSADOR, ELECTRONIC WORD OF MOUTH (e-WOM) DAN CITRA MEREK TERHADAP MINAT BELI PRODUK SUNSCREEN AZARINE - Yulianita Putri Rahma; Mulyo Budi Setiawan (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
Competition in the beauty and skincare industry today is becoming increasingly competitive. As evidenced by the many cosmetic products from local brands that have sprung up in the country. Along with the development of technology, information acquisition about a product can be obtained through experiences from other consumers in cyberspace with a wide range. This has led to a phenomenon related to the use of brand ambassadors, eWOM, and brand images used by companies as marketing efforts to encourage consumers’ buying interest. This test was conducted to test the influence of brand ambassadors, eWOM, and brand image on Azarine’s interest in buying sunscreens. The sample determination technique uses purposive sampling, a criteria for respondents aged 17 years and over. The data collection technique uses a questionnaire with the filling out of 100 respondents. Measurement of research instruments with a likert scale. Testing is carried out by testing the validity, reliability, regression and hypothesis test partially and simultaneously. The resultsof the analysis found that the variables of brand ambassador and eWOM had a positive and insignificant effect on buying interest. On the other hand, brand image variables have a significantand positive effect on buying interest.